Analysis of The Effect of Tax Audits and Collection on Tax Revenue - Hendra Prasetyo (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
Tax revenue is a critical component of the Indonesian State Budget, with tax audits and collection as key mechanisms for optimizing state revenue. This study aims to analyze the effect of tax audits and collection on tax revenue at the Teluk Betung Pratama Tax Office (KPP Pratama), Bandar Lampung, for the 2021-2024 period. This empirical study uses quantitative research methods with secondary data from the Teluk Betung Pratama Tax Office (KPP Pratama) for the 2021-2024 period. Multiple linear regression analysis was conducted to examine the relationship between tax audits, tax collection, and tax revenue. The analysis shows that tax audits have a significant positive effect on tax revenue, while tax collection does not show a significant effect. The tax audit variable shows the highest contribution to optimizing tax revenue